Infrared Sensor System for Mobile-Robot Positioning in Intelligent Spaces - Luis Pallarés Puerto; Felipe Espinosa Zapata; David Salido Monzú; José Luis Lázaro Galilea; Franciso Javier Meca Meca; Ernesto Martín Gorostiza (Sensors, 2011)
The aim of this work was to position a Mobile Robot in an Intelligent Space, and this paper presents a sensorial system for measuring differential phase-shifts in a sinusoidally modulated infrared signal transmitted from the robot. Differential distances were obtained from these phase-shifts, and the position of the robot was estimated by hyperbolic trilateration. Due to the extremely severe trade-off between SNR, angle (coverage) and real-time response, a very accurate design and device selection was required to achieve good precision with wide coverage and acceptable robot speed. An I/Q demodulator was used to measure phases with one-stage synchronous demodulation to DC. A complete set of results from real measurements, both for distance and position estimations, is provided to demonstrate the validity of the system proposed, comparing it with other similar indoor positioning systems.